The Asymptomatic Giant Paraoesophageal Hernia in a Elderly Male Patient - AYAN, Fadıl; TEKSÖZ, Serkan; KOL, Ece; ERSAN, Yılmaz; AYAN, Faruk (Cerrahpaşa Medical Journal, 2014)
Hiatal hernia is identified as migration of the stomach completely or partial whether with other intestinal organs into the thoracic mediastinum. Due to etiopathogenesis is not certain, the incidence seems to be higher in older age. Here we report a case of a giant type 3 hiatal hernia in a 70 year old male patient. Case is presented with arhytmia, dyspnea and chest pain in internal medicine clinic. After a long term medical treatment, the clinical manifestations do not disappear. After the failure of medical treatment as a higher level diagnosis the upper gastrointestinal contrast study has been done to patient showing most of the stomach replaced in to the thoracic cavity. After the diagnosis the patient is referred to our clinic for surgical treatment. Laparotomy was performed. We have seen that whole of the stomach has been migrated to mediastinum from left latero-posterior of esophagus. Reduction, crurorafi and Nissen fundoplication has been performed. Patient discharged from the hospital at 7th day postoperatively without any complication. It has been observed that clinical manifestations disappeared after the operation in the following controls. Most of the patients with hiatal hernia may be asymptomatic, but these cases can also present respiratory, circulatory and gastrointestinal manifestations. Due to the wide spectrum of clinical manifestations these patients may be false diagnosed. Symptomatic patients are treated with medical treatment until the hiatal hernia is diagnosed. It has been reported that delay in diagnosis of hiatal hernia cases which treated medically may cause complications of strangulation and incarceration. Surgical options in surgery are laparoscopic crurorafi and Nissen fundoplication. Technical equipment, experience of surgeon is important in these surgical procedures.